A kiszámítható jövő - András, Ferenc (Kultúratudományi Szemle, 2024)
The calculable future Can the future be calculated? I would like to point out that, from a practical point of view, it is simply counterfactual to give a categorically negative answer to the question. Common sense and science work in the context of calculations. The concept of causality and temporality requires a distinction between events; it assumes uninterrupted continuity and a fixed sequence of elements appearing in the continuity. I argue that in this process, there are privileged positions in terms of calculations: the present in the case of time and the cause within the causal relation.